(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
The present paper translates the poem selected from Waray into English of the Chito S. Roño Literary Awards, and applies New Criticism in the textual analysis. It focuses on the translator’s role as a linguistic and cultural interpreter in faithfully rendering the nuances of the literary text from Waray to English. Before developing a strategy for translating the source text into the target language, translators understand the relationship between the source language and culture. The translation of culturally specific items is central to the current study. Strategies are based on Newmark’s semantic translation, Koller’s formal expressive equivalence, Reiss’ text types, and Vinay and Darbelnet’s Model giving a domesticated or foreignized effect on the product of translation. In addition to transferring meaning, the text’s cultural identity is emphasized as a pillar of the translation process. The collection of poetry talks about the universal themes of love and relationships, the essence of family life, life’s journey and the dynamics of society while the images and objective correlatives effectively represent human conditions. Symbolisms and central metaphors reflect the values and human experiences of individuals. The poems do not have set rhymes and meter but are well-written in subtle, metaphorical lines, mirror life, and celebrate the Waray language, reveal the Waray sensibilities, and reflect the Waray ideals and values which are also universal ideals and values proving that the Waray language and culture are not inferior to the rest of the world.